Inflation targeting in Brazil: what difference does a year make? - Dionísio Dias Carneiro (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
The adoption of inflation targeting as a monetary policy strategy in Brazil was a convenient way to replace exchange rate rule by targeted inflation in an effort to anchor inflation expectations. This paper briefly evaluates the inflation target experience from three viewpoints: reasons behind the success, difficulties regarding forecasting and the risks ahead. It analyses the factors behind the success as well as the way initial doubts and a second round of mistrust were successfully dealt with. It looks at the empirical difficulties to estimate a reliable Demand Function and examines evidence on the persistence of high interest rates as captured by a Taylor rule. It points out to possible signaling problems in the transmission mechanism that might lead to a weakening of the confidence in the strategy in the future. Section 3 draws conclusions on risks that emerged together with favorable outcomes of the first year. There has been a substantial progress in the overall confidence in monetary policy's management. Inflation targeting has certainly played a relevant role in this gain. However, it looks like we have not got rid of the "thin ice economy" riding in the post-Real era, since dependence of inflation on foreign exchange availability is still high. Thus the Brazilian economy is still excessively dependent on international liquidity fluctuations. As it happened in the past six years, because of the combination of the size of interest rate movements with the persistence of effects, a double barrel destructive effect on investment and banking, good scenarios tend to be too good, and bad scenarios are seen as terrible for assets markets. An appendix note was written by Thomas Wu on the problem of finding a measurement of the output gap for the Brazilian economy.
Keywords: E52; E65; 330